1997
DOI: 10.2307/3433348
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Patients with Chemical Injury and Sensitivity

Abstract: 417-436 (1997)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 39 publications
(46 reference statements)
0
45
0
Order By: Relevance
“…Only one published text is cited in support of this. 13 A table in this publication shows 12 out of 14 patients (85.7%) with at least one metabolic test result outside the cited normal range. However, there are several deficiencies with this interpretation.…”
Section: Porphyriamentioning
confidence: 87%
See 1 more Smart Citation
“…Only one published text is cited in support of this. 13 A table in this publication shows 12 out of 14 patients (85.7%) with at least one metabolic test result outside the cited normal range. However, there are several deficiencies with this interpretation.…”
Section: Porphyriamentioning
confidence: 87%
“…No single widely accepted test of physiologic function has been shown to correlate with symptoms". 12 Ziem and Mctamney 13 showed that, of 90 subjects, over 50% often reported the following symptoms (either daily or several times a week): headache, weakness, inability to concentrate, memory problems, low energy, nasal congestion, throat soreness or tightness, and joint discomfort. At least 30% reported other symptoms aVecting most body systems including: abdominal pain, nausea, visual changes, chest tightness, muscle discomfort, skin rash, sleep disturbance, and urinary disturbance.…”
Section: Definition Of Mcsmentioning
confidence: 99%
“…Conversely, symptoms among Cambodia veterans 1 were similar to those found in a group of MCS Syndrome patients studied by Ziem and McTamney. 21 We used the same questions about chemical exposure as were used by Davidoff and Keyl 11 ; Ziem and McTamney 21 also used these questions. However, in our study, a much lower percentage of subjects complained following exposure to certain chemicals than was the case in MCS Syndrome patients in the Ziem and McTamney study.…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol was assessed at four times during the day : 7± 8 AM; noon; 4± 5 PM; and 11± 12 PM. Ten of 11 tested had elevated levels at 11± 12 PM, which likely contributes to sleep disruption, commonly reported by MCS patients (Ziem and McTamney 1997). Controlling the ratio of carbohydrate to protein calories to roughly 2 to 1 and giving preference to lowglycemic carbohydrates could reduce this effect, because cortisol is released when the body corrects the blood sugar drop resulting from insulin secretion needed for carbohydrate breakdown.…”
Section: Some Potentially Treatable Consequences Of Chemical Injurymentioning
confidence: 99%
“…Many chemicals have not been evaluated for their ability to disrupt porphyrin metabolism in animals or humans. Of 14 patients with MCS tested through the Mayo Medical Laboratory, 12 had evidence of porphyrin disturbance (Ziem and McTamney 1997). Although the degree of porphyrin disturbance was milder than with congenital porphyria, 6 of the 12 affected patients had involvement of more than one enzyme in porphyrin metabolism.…”
Section: Petrochemical-induced Injurymentioning
confidence: 99%